COST EFFECTIVENESS ANALYSIS BETWEEN ASPIRIN AND CITICOLINE IN STROKE PATIENT IN PROF DR MARGONO SOEKARJO HOSPITAL PURWOKERTO - Didik Setiawan (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2014)
Stroke is the third highest cause of death after heart disease and cancer. An appropriate therapy decision is important because it related to many factors such as cost and quality of life. Most of Indonesian physicians’ use citicoline and Aspirin for stroke patients. A Cohort Retrospective study was performed to 40 patients with aspirin and 77 patients with citicoline. Secondary data such as cost, length of stay (LoS) was collected from medical records. Furthermore, patient health level was measured by National Institute of Health Stroke Scale (NIHSS) which was collected from patient directly. The average of patients’ age was 60.59±11.31 years old. The NIHSS showed no significant difference between aspirin (2.58±2.93) and citicoline (3.10±2.90) groups. Otherwise, LoS was different between two groups (p value 0.000). The average of total cost in aspirin group (IDR 2,593,250.00) was lower than citicoline groups (IDR 11,384,210.00) and the differences were statistically siginificant. The Incremental Cost Effectiveness Ratio (ICER) between aspirin compared to citicoline was IDR 16,905,692.31 per quality of life. Aspirin was strongly dominated to citicoline in cost, LoS and NIHSS.